Factors influencing farmers' utilisation of marketing information sources: some empirical evidence from Pakistan. Issue 1 (2nd January 2023) - Yaseen, Muhammad; Ahmad, Mokbul Morshed; Soni, Peeyush; Kuwornu, John K. M.; Saqib, Shahab E.
ABSTRACT: This study empirically investigates the factors influencing Pakistani cotton farmers' utilisation of marketing information sources. Data were collected by face-to-face, interviewing 399 cotton farmers. Factors and variations of the utilisation of marketing information sources were analysed using multivariate probit, chi-square, and descriptive statistics. The results revealed significant variations among farmers in the utilisation of mobile phones, internet, television, radio, newspapers, extension services, market commission agents, and fellow farmers. The findings highlighted the usage of several combinations of ICT, traditional media, extension services, and farmers' social relations. Furthermore, key socio-economic and institutional factors influencing marketing information utilisation were discussed.